Experts’ Views on Integrating Contextual Case-Based Learning Method into English Writing Textbook - Rika; Siagian, Sahat; Sibuea, Abdul Muin; Setiawan, Deny (Forum for Linguistic Studies, 2025)
This study investigates experts’ perspectives on integrating contextual case-based learning (CCBL) methods into essay writing textbooks designed for English Language Teaching (ELT) program students. The primary objective is to evaluate the effectiveness and suitability of incorporating CCBL approaches to enhance writing skills within ELT curricula. To achieve this, a descriptive quantitative research design was employed. Data were collected through questionnaires comprising both closed- and open-ended items, distributed to three groups of experts: instructional design experts, content/material specialists, and media experts. The study sought to capture a comprehensive evaluation from different professional viewpoints on the textbook’s design and pedagogical approach. Analysis of the collected data revealed a total average score of 3.76 out of 5, indicating strong agreement among the experts that the integration of CCBL methods in essay writing textbooks is beneficial and appropriate. Experts highlighted the contextualized nature of case-based learning as an effective way to engage students, facilitate critical thinking, and improve practical writing skills by connecting theoretical knowledge with real-life scenarios. In conclusion, the study supports the adoption of contextual case-based learning methods in essay writing textbooks as an effective instructional strategy for ELT students. Such integration not only enhances students’ writing competence but also encourages deeper engagement with the learning material. The study recommends that textbook developers and educators consider CCBL approaches when designing writing curricula. Additionally, future research is encouraged to explore the application of contextual case-based learning methods in textbooks focused on other key language skills, including speaking, listening, and reading, to further enrich English language education.